Effect of Time-Based Conflict on Employee Productivity: Does Altruism Matter? A Reflection from star-rated Hotels in Kenya - Barsulai , Stella C. (African Journal of Education,Science and Technology (AJEST), 2022)
The current study sought to assess the influence of altruism on the relationship between time-based conflict and employee productivity in star-rated hotels in Nairobi-Kenya. The study adopted explanatory design. A total of 4725 employees from 30 star rated hotels were targeted. Nassiuma formula (2000) was used to sample 214 employees to answer questionnaires. Stratified sampling was employed to select employees from the departments chosen. Bias Corrected Bootstrapping of SEM, using AMOS version 5, in SPSS version 23 was used to test the hypotheses. The results showed that for each unit increase in time-based conflict, there was a decrease in employee productivity. These findings illustrated that the conflict experienced by employees negatively affects employee productivity. The results further showed that when Altruism is exhibited, it reduces the influence of time-based conflict on employee productivity. This shows the importance of employees exhibiting altruism to reduce the effect of the conflict for employee productivity to be achieved. The study findings will be insightful to management in the hotels to develop guidelines to help hotel managers and supervisors improve employee productivity through the use of altruistic behavior.